A GIS based air quality system for the Apulia region, southern Italy. (1st January 2011) - Schipa, I.; Mangia, C.; Tanzarella, A.; Conte, D.; Marra, G.P.; Rizza, U.
A GIS based air quality modelling system has been developed in Apulia region in the Southern – Italy, to support local authorities in air quality management. Meteorological and dispersion simulations were performed for the year 2005. Predictions have been compared with concentration data from the air quality monitoring network. Results evidence a good correlation between predictions and measurements for O3, NO2, SO2, with a light tendency to underestimate measured data in urban stations. Overall the model tends to underestimate CO measurements. The uncertainty of the predictions are analysed and discussed in terms of the emission calculations, dispersion modelling and monitoring sites.